Design and synthesis of the first ferrocenylsiloxane urea: Structure and properties. (14th December 2015) - Dascalu, Mihaela; Balan, Mihaela; Shova, Sergiu; Racles, Carmen; Cazacu, Maria
Graphical abstract: The first cyclic compound containing urea moieties as structural units was obtained through the reaction of 1, 1′-diisocyanatoferrocene with 1, 3-bis(aminopropyl)tetramethyldisiloxane. Its crystal structure was confirmed by single crystal X-ray diffraction. The co-existence of polar and nonpolar moieties, the compound is able to self-assemble in CHCl3 in quasi-spherical aggregates with vesicle-like aspect. Abstract: The first cyclic ferrocenylsiloxane-urea, {1, 1′-ferrocene-diurea-[1, 3-bis(propylene)tetramethyldisiloxane]} (FSU), has been formed by reacting 1, 1′-ferrocenediisocyanate with 1, 3-bis(aminopropyl)-tetramethyldisiloxane in a chloroform–toluene mixture. The ferrocenylsiloxane urea was structurally characterized by FTIR and 1 H NMR spectroscopy, elemental analysis, mass spectrometry (ESI-MS), and single crystal X-ray diffraction. The electrochemical behavior was studied by cyclic voltammetry. FSU exhibited one reversible redox wave with a redox coupling E 1/2  = 0.107 V (FSU-CHCl3 ), and 0.158 V (FSU-DMSO). The 1 H NMR analysis revealed that the ferrocenylsiloxane urea presents association capacity in chloroform, behavior sustained by transmission electron microscopy. The temperature dependence of the hydrogen bonds in the solid state complex was investigated by IR-spectroscopy.